High Figure of Merit Magneto‐Optical Ce‐ and Bi‐Substituted Terbium Iron Garnet Films Integrated on Si. Issue 16 (31st May 2021) - Fakhrul, Takian; Tazlaru, Stana; Khurana, Bharat; Beran, Lukáš; Bauer, Jackson; Vančík, Michal; Marchese, Ariane; Tsotsos, Ekaterina; Kučera, Miroslav; Zhang, Yan; Veis, Martin; Ross, Caroline A.
Abstract: Films of polycrystalline terbium iron garnet (TbIG), cerium‐substituted TbIG (CeTbIG), and bismuth‐substituted TbIG (BiTbIG) are grown on Si substrates by pulsed laser deposition. The films grow under tensile strain due to thermal mismatch with the Si substrate, resulting in a dominant magnetoelastic anisotropy which, combined with shape anisotropy, leads to in‐plane magnetization. TbIG has a compensation temperature of 253 K which is reduced by substitution of Ce and Bi. The Faraday rotation at 1550 nm of the TbIG, Ce0.36 TbIG, and Bi0.03 TbIG films is 5400 ± 600° cm −1, 4500 ± 100° cm –1, and 6200 ± 300° cm −1, respectively, while Ce0.36 TbIG and Bi0.03 TbIG exhibit lower optical absorption than TbIG, attributed to a reduction in Fe 2+ and Tb 4+ absorption pathways. The high Faraday rotation of the films, and in particular the high magneto‐optical figure of merit of the Bi0.03 TbIG of 720° dB −1 at 1550 nm, make these polycrystalline films valuable for applications in integrated photonics. Abstract : This article presents developments in the integration of high figure of merit (FoM) magneto‐optical (MO) rare‐earth garnet films onto silicon for use in optical isolators. TbIG, Ce0.36 TbIG, and Bi0.03 TbIG garnet thin films are grown on Si substrates by pulsed laser deposition. The films have a Faraday rotation that is almost twice as high as previous reports for polycrystalline MO garnet films. Ce0.36 TbIG and Bi0.03 TbIG exhibit lower optical absorption than TbIG, attributed to a reduction in Fe 2+ and Tb 4+ absorption pathways. The MO FoM of Bi0.03 TbIG is 720 o dB −1, similar to that of BiYIG films but without the need for a YIG seedlayer for integration.